VAL - Vehicular adaptation layer, for NDN - Pereira, João Fernandes (2023)
High mobility and intermittent connectivity of nodes are the main characteristics of Vehicular Ad-Hoc Networks (VANETs). These two aspects cause problems in traditional IP networking. Named Data Networking (NDN) is presented as one of the most promising paradigms for the future Internet. NDN is a data-centric architecture. It relies on data names instead of the host's location to make forwarding decisions. In NDN, any node can be a candidate for supplying the desired content. This feature makes the NDN architecture appealing for VANET scenarios (V-NDN). This paper presents a strategy for applying NDN to VANETs with support for geographical-based forwarding. For this purpose, an additional layer called Vehicular Adaptation Layer (VAL), is proposed to illustrate how this can be performed without altering the NDN primitives and core structure. VAL provides: 1) a mechanism to bind NDN data names to the producers' and consumers' geographic areas; 2) a discovery mechanism to find producers' areas and 3) the capability of implementing, in a plug-and-play manner, geo-forwarding algorithms capable of guiding Interests towards data producers and Data packets towards data consumers.